Phytoplankton and nutrients studies in Magu bay, Speke gulf, Lake Victoria, (Tanzania) following the 2001 principal rain season - Machiwa, JF; Lugomela, C; Muzuka, ANN (Tanzania Journal of Science, 2021)
Phytoplankton abundance and species composition in relation to some physico-chemical parameters were studied in Magu Bay, Lake Victoria, in May 2001. Investigations on the influence of Simiyu River on the biological and physical characteristics of the Bay were carried out. Surface and bottom currents flowed in the northeast direction close to the river mouth but were completely reversed after about 1.5 km from the river mouth. Most suspended particles brought in by the river were deposited within 0.5 km after entering the lake. Nutrient concentrations were generally high towards the eastern part of the bay as compared to the rest of the bay area probably due to the reversal in the direction of current flow. Phytoplankton were generally dominated by the cyanobacteria Microcystis and Anabaena species though the diatoms Nitzschia and Melosira species were more abundant in some sampling stations. Phytoplankton abundance ranged from 500 cells ml-1 at stations LV36 and LV37 to 1440000 cells ml-1 at station LV1. The high abundance encountered at stations LV1, LV2, and LV3 is assumed to be due to formation of surface scum of the gas vacuolated Microcystis cells as a result of wind action. Phytoplankton production was possibly light limited in areas with simultaneously high nutrient concentrations and high turbidity. More data are required to corroborate the current study and to have a full picture of the influence of the river during different seasons.